Extrapulmonary manifestations of COVID-19 in children: a comprehensive review and pathophysiological considerations (2020)
Objective: The aim of this review was to summarize the most common extrapulmonary manifestations in pediatric patients with COVID-19, as well as to discuss clinical, epidemiological, and pathophysiological aspects of these clinical presentations in children. Source of data: An extensive search of literature was performed in order to identify pediatric cases with extrapulmonary manifestations between January 1, 2020 and June 21, 2020. Generic keywords, such as “Novel coronavirus” or “Novel coronavirus 2019” or “2019 nCoV” or “COVID-19” or “SARS-CoV-2” were searched on PubMed database, associated either with age filters or generic pediatric terms. Summary of findings: A total of 28 articles, including 199 patients, were considered suitable to review and data extraction. The main findings were summarized in tables. The main non-pulmonary manifestations in pediatric patients, in decreasing order of frequency, were gastrointestinal, renal, cardiovascular, neurological, hematological and lymphatic, cutaneous, hepatic, ocular, olfactory, and gustatory. Multisystem impairment and Kawasaki-like disease were also described. Conclusions: Differences in immune response of children and variations of tissue expression of angiotensin converting enzyme 2, the virus receptor, are likely to influence clinical, epidemiological, and pathophysiological patterns of the disease